The Guidelines for consumption of The Four Necessities to Appreciate the True Value: - Thaobuppha, PhraPrecha (Journal of Buddhist Innovation Review, 2025)
The Guidelines for consumption of The Four Necessities to Appreciate the True Value. —food, robes, shelter, and medicine—by monks, both in the past and present. The goal is to consume mindfully and with moderation, not driven by desires and attachments. It emphasizes the importance of Yoniso Manasikara (wise attention) in consumption, aiming to sustain life and advance in monastic virtues, thus alleviating suffering. The Buddha taught principles to consider before using the Four Requisites, which can be summarized as follows: consumption should be mindful and moderate, for the purpose of maintaining one's existence, rather than indulging in desires and cravings. The goal of the monastic life is to attain enlightenment. However, consumption practiceshave changed over time, and thus it is important to promote awareness of Buddhist principles in consumption s that monks may practice accordingly. This will help create a model society amidst the consumerist age